Cost-effectiveness of strategies to increase cervical screening uptake at first invitation (STRATEGIC). (June 2018) - Tsiachristas, Apostolos; Gittins, Matthew; Kitchener, Henry; Gray, Alastair
Objective: To assess the cost-effectiveness of strategies to increase cervical cancer screening uptake at first invitation (STRATEGIC trial). Methods: We performed an economic analysis alongside the STRATEGIC trial, comparing each of seven novel interventions for improving cervical screening uptake with control general practices in Greater Manchester and Grampian (United Kingdom). A template was developed to measure the intervention costs. Trial estimates of screening uptake were combined with data from the literature to estimate healthcare costs of each intervention. The added lifetime costs and quality adjusted life years (QALYs) of attending cervical screening were estimated by a systematic literature review, with relevant results pooled and weighted by study quality. Trial results and estimated lifetime costs and benefits of screening were then combined in a decision analytic model, giving an incremental cost per QALY gained for each intervention. Uncertainty was addressed in probabilistic and univariate sensitivity analyses. Results: Intervention costs per screening round per woman attending varied from about £1.20 (2014 UK) for the nurse navigator intervention to £62 for the unrequested HPV self-sampler kit. The meta-analysis revealed a lifetime discounted benefit from screening of 0.043 QALYs per woman attending, at an additional lifetime discounted cost of £234. The incremental cost per QALY gained in all interventions was below £13, 000. Probabilistic sensitivity analyses suggested that only unrequested self-sampling and timed appointments have a high probability of being cost-effective. Conclusions: Unrequested self-sampling and timed appointments are likely to be cost-effective interventions. Further research is required on the duration of effects and on implementing combinations of interventions.